Avaliação remota da tolerância ao exercício e das variáveis fisiológicas no Teste de Degrau de seis minutos e nas Atividades de Vida Diária por meio de Tecnologia Vestível em pacientes após hospitalização pela COVID-19 - Viana, Daiane Roberta (2022)
Introduction: Patients with COVID-19 may have different impairments, especially in the most severe cases requiring hospitalization and intensive care. These impairments may be present even after hospital discharge, therefore, assessing exercise intolerance, the behavior of regulators and the level of physical activity of patients become fundamental. Among the forms of evaluation are the Six-Minute Step Test (6MST), Activities of Daily Living (ADL) and the use of wearable technology. Therefore, this dissertation resulted in two studies: Study 1 – Objectives: Verify and identify predictors of exercise intolerance assessed by the remote 6MST and compare performance, peripheral oxygen saturation (SpO2), and the feeling of dyspnea and fatigue in the test among patients who were hospitalized for up to 10 days with those who stayed more than 10 days due to COVID-19. Methods: This was a cross-sectional observational study, carried out by telemonitoring, of patients on average 30 days after hospital discharge due to COVID-19. The patients were evaluated by video call in two moments, the first moment was an initial evaluation for data recording and application of the inclusion criteria, and in the second moment the 6MST was performed. For monitoring during the test, patients received a 20-centimeter-high step in their homes, an automatic blood pressure device, a pulse oximeter and a modified Borg scale (0-10). Patients were divided into two groups: those who were hospitalized for up to 10 days (G≤10) and those who were hospitalized for more than 10 days (G>10). Results: Eighty patients were evaluated and it was verified that the length of hospitalization, cardiovascular and respiratory diseases, age and gender had a significant effect (adjusted R2=0.40) on the mean number of steps in the 6MST. In addition, 44 were hospitalized for up to 10 days (G≤10) and 36 for more than 10 days (G>10), and it was possible to verify that there was a significant difference between the groups regarding the need for intensive care (p<0.01), 6MST performance (p=0.04) and in the presence of oxygen desaturation (p<0.02). Conclusion: With the present study, it was possible to verify that the length of hospitalization, cardiovascular and respiratory diseases, age and gender had an influence on the exercise intolerance of patients after hospitalization for COVID-19 and that patients who were hospitalized for more than 10 days, showed greater exercise intolerance and desaturated more than patients who were hospitalized for up to 10 days, even 30 days after hospital discharge. Study 2 – Objectives: To characterize the responses of physiological variables during the simulation of an ADL circuit in relation to the physiological responses presented in the remote 6MST of patients after hospitalization for COVID-19 through wearable technology. In addition to verifying the association of physiological responses during ADL, exercise tolerance is verified by 6MST and physical activity level. Methods: This was a cross-sectional observational study carried out by telemonitoring patients after hospital discharge due to COVID-19. The patients underwent an initial assessment via video call and those eligible for the study received the material to perform the 6MST and the ADL circuit at their homes, including the smart T-shirt, made up of sensors that estimate the Frequency variables Respiratory (BR); Tidal volume (VT); Minute Ventilation (VE); Heart Rate (HR) and Cadence (CAD). For the evaluations, the patients were instructed to use the smart shirt for eight consecutive days for at least eight hours a day, and on the seventh day the 6MST was performed and on the eighth day an ADL circuit, both by video call. Results: Thirty-seven patients were evaluated and it was possible to verify significant differences between the ventilatory and cardiac variables during the execution of the 6MST with the ADL circuit and a moderate positive correlation between performance in the 6MST by the number of steps with CAD during the monitoring of the free ADL (R=0.594, p=0.000), correlation between performance in 6MST with the ventilatory variables in 6MST and in ADL1, however, there was no correlation between CAD in the monitoring of free ADL with the ventilatory and cardiac variables. There was also a moderate negative correlation between CAD and length of hospital stay (R= -0.590, p=0.000), and a weak negative correlation between CAD and the need for intensive care (R= -0.379, p=0.027) and 6MST performance with length of stay hospitalization (R= -0.374, p=0.023). Conclusion: The responses of the VE and HR variables during the ADL reached lower values when compared to the values reached in the 6MST. Both ventilatory and cardiac variables in 6MST were able to moderately predict the responses of the same variables in ADL, as well as the performance in 6MST was able to predict the level of physical activity, with longer hospitalization time and the need for intensive care negatively influencing the patients' exercise tolerance after 30 days of hospital discharge due to COVID-19.